Critical reflections on synthetic gene design for recombinant protein expression. (June 2016) - Parret, Annabel HA; Besir, Hüseyin; Meijers, Rob
Highlights: Codon optimization can dramatically boost protein expression. Replacement of rare codons can affect protein folding. Synthetic gene design would benefit from novel insights in protein translation. Expression vectors could be redesigned for optimal translation initiation. Abstract : Gene synthesis enables the exploitation of the degeneracy of the genetic code to boost expression of recombinant protein targets for structural studies. This has created new opportunities to obtain structural information on proteins that are normally present in low abundance. Unfortunately, synthetic gene expression occasionally leads to insoluble or misfolded proteins. This could be remedied by recent insights in the effect of codon usage on translation initiation and elongation. In this review, we discuss the interplay between optimal gene and vector design to enhance expression in a particular host and highlight the benefits and potential pitfalls associated with protein expression from synthetic genes.